Administrative Privatization Trend of Sport Clubs Participating in Iraqi Soccer Primer League - Radi, Haider; Hazza, Abdullah (Journal of Physical Education, 2019)
The aim of the research was to identify the administrative trend towards the privatization of sports clubs of Baghdad participating in the Iraqi Premier soccer League from the coaches and players point of view. The researchers used the descriptive method and the sample of the research were(290)  coaches and players of Baghdad clubs participating in the Iraqi soccer Premier League for the season (2018-2019). The researcher suggested (25) item for the scale and presented it to (17) experts who agreed to (20) items, then the scale was applied on the sample (180) then it was applied on the subjects to come up with the results of the study. The results showed a great trend of coaches and players of the Baghdad clubs participating in the Iraqi soccer Premier League towards the privatization of sports.